2012
DOI: 10.1002/ajim.22128
|View full text |Cite
|
Sign up to set email alerts
|

Safety, incentives, and the reporting of work‐related injuries among union carpenters: “You're pretty much screwed if you get hurt at work”

Abstract: There are multiple layers of disincentives to the reporting of work-related injuries that hamper understanding of risk and pose threats to workplace safety and productivity. These pressures do not arise in a vacuum and are likely influenced by a host of contextual factors. Efforts that help us understand variation across jobsites and time could be enlightening; such inquiries may require mixed methodologies and should be framed with consideration for the upper tiers of the public health hierarchy of hazard con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 27 publications
1
36
0
1
Order By: Relevance
“…Lipscomb et al looked at the job consequences of injury reporting among carpenters and also found an atmosphere of intimidation on construction sites. 47 In addition to nonretaliation for hazard reporting, we suggest that coworker and supervisor social support play a critical role in safety climate for Hispanic construction workers. Previous research found that Hispanic construction workers consistently identified an absence of mutually respectful attitudes and behaviors as an impediment to safety in construction.…”
Section: Discussionmentioning
confidence: 87%
“…Lipscomb et al looked at the job consequences of injury reporting among carpenters and also found an atmosphere of intimidation on construction sites. 47 In addition to nonretaliation for hazard reporting, we suggest that coworker and supervisor social support play a critical role in safety climate for Hispanic construction workers. Previous research found that Hispanic construction workers consistently identified an absence of mutually respectful attitudes and behaviors as an impediment to safety in construction.…”
Section: Discussionmentioning
confidence: 87%
“…48,49 For example, programs that provide incentives to reduce reporting of injuries may have the unintended consequence of minimizing reporting without altering actual injury rates, and also shift the burden of responsibility for injury reduction to individual workers without attending to needed multi-level supports in the work environment. 50 …”
Section: Indicators Of Integrationmentioning
confidence: 99%
“…To combat this, some employers have implemented safety incentive programs, such as those that use injury-based safety performance metrics to evaluate overall worksite safety and reward workers. However, these lagging indicator-based programs may discriminate against injured workers (2) and may reduce injury reporting (3, 4). …”
mentioning
confidence: 99%